Fluoroscopy, CT, and MR imaging characteristics of a novel primarily bioresorbable flow-diverting stent for aneurysms. Issue 6 (December 2022) - Morrish, Rosalie; Corcoran, Ronan; Cooke, Jillian; Eesa, Muneer; Wong, John H; Mitha, Alim P
Background: Five to ten percent of the global population have unruptured intracranial aneurysms, and ruptured brain aneurysms cause approximately 500, 000 deaths a year. Flow-diverting stent treatment is a less invasive intracranial aneurysm treatment that induces aneurysm thrombosis. The imaging characteristics of a novel primarily bioresorbable flow-diverting stent (BFDS) are assessed in comparison to the leading metal stent using fluoroscopy, CT, and MRI. Methods: X-ray/fluoroscopic images of stents were taken using a human cadaveric skull model. CT and MRI were acquired using silicone flow models of residual aneurysms. Images were analyzed with Likert scales in anonymous surveys by neurointerventionalists. Quantitative measurements of radiographic density (CT) and artifact boundary size (CT & MRI) were also obtained. Results: Visibility of the BFDS on X-ray was less than the metal stent but deemed adequate for deployment and intraprocedural assessment. The metal stent was more radiopaque than the BFDS on CT, but qualitative assessment was not significantly different for the two stents. MRI imaging was significantly better using the BFDS in terms of overall artifact and intraluminal assessment. Conclusions: The BFDS has adequate visualization on X-ray/fluoroscopy and should be clinically acceptable for fluoroscopic deployment. On MRI, there is less quantitative artifact as well as overall improved qualitative assessment that will allow for more detailed non-invasive imaging follow-up of treated aneurysms, potentially reducing the need for digital subtraction catheter angiography.